Bridging citizen science and science communication - Roche, Joseph (Frontiers Media SA, 2024)
The growth of public engagement in science is supported by two complementary fields of research and practice: citizen science and science communication. Presenting unique opportunities for the development of science in society, the two fields serve as agents of change. Both independently and in tandem, science communication and citizen science catalyze scientific innovations, raise environmental awareness, drive informed resource management, and promote sustainable development.
Keywords: multiple stakeholders, participatory science communication, theory-practice, science and society, dialogue, community science, public participation in science, public engagement; Citizen Science; SCIENCE COMMUNICATION